Adhesive for optical member and optical element
The adhesive for optical members, composed of specific components and ratios, addresses the issues of peeling and durability by minimizing curing shrinkage and enhancing mechanical strength and light transmittance, ensuring strong and durable bonding of optical members with metal films.
Patent Information
- Application Number
- JP2023181140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
Conventional adhesives for optical members tend to peel off metal films when hardened, and their durability decreases in high-temperature environments, leading to reduced adhesive strength.
An adhesive comprising an aromatic hydrocarbon resin, a mono(meth)acrylic monomer, a rubber component with (meth)acrylic groups, a photopolymerization initiator, and a silane coupling agent, with specific ratios and properties to minimize curing shrinkage and enhance mechanical strength and light transmittance.
The adhesive effectively prevents peeling of metal films, maintains high durability and light transmittance, and ensures strong adhesion even in high-temperature environments.
Smart Images

Figure 2025070655000001 
Figure 2025070655000002 
Figure 2025070655000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive for optical members and an optical element. [Background technology]
[0002] Currently, various kinds of optical elements have been developed, and optical members such as lenses and prisms are bonded to various members. Adhesives having optical transparency are preferably used for bonding such optical members. For example, Patent Document 1 describes an adhesive for optical members that contains a compound having an oxiranyl group and an onium salt compound.
[0003] In recent years, a stereoscopic imaging device has also been proposed in which two optical members (light control panels) each having a plurality of light-reflecting surfaces made of metal films are bonded together to form a two-dimensional or three-dimensional image in the air. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-27270 Summary of the Invention [Problem to be solved by the invention]
[0005] However, when an optical member having a metal film on its adhesive surface is bonded with a conventionally known adhesive for optical members, the metal film may peel off when the adhesive for optical members is cured or when the optical member is used. In addition, the optical member may be exposed to a high-temperature environment, in which the cured product of the adhesive for optical members may deteriorate, resulting in a decrease in adhesive strength with the optical member.
[0006] The present invention has been made in view of the above circumstances. Specifically, an object of the present invention is to provide an adhesive for optical components that is unlikely to cause peeling of the metal film even when used to bond optical components that include a metal film on the bonding surface, and that can give a cured product that is highly durable and has high light transmittance, and an optical element using the adhesive. [Means for solving the problem]
[0007] The present invention provides the following adhesive for optical members. [1] An adhesive for optical components comprising: (A) an aromatic hydrocarbon resin having a total light transmittance of 80% or more in the visible light region at a thickness of 1 mm, measured in accordance with JIS K7361-1; (B) one or more (meth)acrylic monomers selected from a mono(meth)acrylic monomer having one (meth)acrylic group in one molecule and a di(meth)acrylic monomer having two (meth)acrylic groups in one molecule; (C) a rubber component having a (meth)acrylic group; (D) a photopolymerization initiator; and (E) a silane coupling agent, wherein the amount of the (B) (meth)acrylic monomer per 100 parts by mass of the (A) aromatic hydrocarbon resin is 30 parts by mass or more and 190 parts by mass or less. [2] The adhesive for optical components according to [1], wherein the total amount of the (B) (meth)acrylic monomer and the rubber component having a (meth)acrylic group per 100 parts by mass of the (A) aromatic hydrocarbon resin is 50 parts by mass or more and less than 300 parts by mass. [3] The adhesive for optical components according to [1] or [2], wherein the (C) rubber component having a (meth)acrylic group is at least one selected from the group consisting of polyurethane (meth)acrylate oligomer, polyisoprene (meth)acrylate oligomer, and polybutadiene (meth)acrylate oligomer. [4] Apply a coating of 100 μm thickness and expose to 3000 mJ / cm of light with a wavelength of 365 nm. 2 The adhesive for optical members according to any one of [1] to [3], wherein when a tensile test is carried out at 25°C and a tensile speed of 20 mm / min on a cured product produced by irradiation and having a width of 10 mm and a length of 30 mm, the elongation at break is 30% or more. [5] The adhesive for optical members according to any one of [1] to [4], wherein at least a portion of the adhesion surface of the adherend comprises a metal film.
[0008] The present invention provides the following optical element. [6] An optical element comprising: a first optical member, a second optical member, and an adhesive layer that bonds the first optical member and the second optical member, wherein the adhesive layer is a cured product of the adhesive for optical members described in any one of [1] to [5]. [7] The optical element described in [6], wherein the first optical member and / or the second optical member includes a metal film in an area adjacent to the adhesive layer. [8] The optical element according to [6] or [7], wherein at least one of the first optical member and the second optical member has an uneven portion in an area adjacent to the cured product. [9] The optical element according to [6], which is an optical imaging element.
[10] The optical element according to [6], which is an optical imaging element for vehicle use. Effect of the Invention
[0009] The present invention aims to provide an adhesive for optical components that, when used to bond optical components containing a metal film on the bonding surface, is less likely to cause peeling of the metal film and produces a cured product that is highly durable and has high light transmittance, and an optical element using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0011] 1. Adhesives for optical components The adhesive for optical members of the present invention is preferably used when adhering optical members that include a metal film on at least a part of the adhesive surface. However, the use of the adhesive for optical members of the present invention is not limited thereto, and it may be used, for example, for adhering optical members that do not include a metal film. It may also be used as an adhesive for adhering members other than optical members.
[0012] As described above, when an optical component having a metal film on its bonding surface is bonded with a conventional adhesive for optical components, the metal film may peel off when the adhesive for optical components is cured. In addition, there is also a problem that the cured product of the adhesive for optical components itself deteriorates over time.
[0013] The inventors of the present invention have conducted extensive research and have found that the influence on the metal film and the deterioration of the adhesive for optical members over time are closely related to the amount of shrinkage during curing of the adhesive for optical members and the extensibility of the cured product of the adhesive for optical members. Therefore, the adhesive for optical members of the present invention includes (A) an aromatic hydrocarbon resin, (B) a (meth)acrylic monomer, (C) a rubber component having a (meth)acrylic group (hereinafter also referred to as "rubber component (C)"), (D) a photopolymerization initiator, and (E) a silane coupling agent. In this specification, the term "(meth)acrylic" means methacryl, acrylic, and both of these. In addition, in the adhesive for optical members of the present invention, the amount of (B) (meth)acrylic monomer relative to the amount of (A) aromatic hydrocarbon resin is within a predetermined range. The reason why the above problem can be solved by such an adhesive for optical members is considered to be as follows.
[0014] In the adhesive for optical members of the present invention, (A) an aromatic hydrocarbon resin and (B) a (meth)acrylic monomer are combined. Therefore, the adhesive for optical members has photocurability, and the mechanical strength and heat resistance of the cured product are very good. Here, if the amount of (B) (meth)acrylic monomer is excessively large, or if the curing shrinkage of the (meth)acrylic monomer is large, a force is likely to be applied to the adhesive surface of the optical member when the adhesive for optical members is cured, and in particular, if a metal film is present on the adhesive surface, the metal film may be peeled off. In contrast, in the adhesive for optical members of the present invention, the amount of (B) (meth)acrylic monomer relative to the amount of (A) aromatic hydrocarbon resin is a certain amount or less. Furthermore, the (B) (meth)acrylic monomer is monofunctional or bifunctional. Therefore, the adhesive for optical members has a small amount of curing shrinkage, and is unlikely to affect the metal film, etc.
[0015] In addition, the adhesive for optical members of the present invention contains a rubber component (C) containing a (meth)acrylic group, and the rubber component (C) polymerizes with the (meth)acrylic monomer (B). As a result, the rubber component (C) is uniformly dispersed and arranged throughout the cured product of the adhesive for optical members, and the cured product has very good elongation. In other words, even if the optical member is deformed due to the application of an external force or expansion and contraction caused by heat, the cured product of the adhesive for optical members can follow the optical member, and peeling at the interface between them is unlikely to occur over a long period of time. Furthermore, since the adhesive for optical members of the present invention contains a silane coupling agent (E), the adhesive between the cured product of the adhesive for optical members and various optical members is very strong. Therefore, the above-mentioned effects can be obtained. Hereinafter, each component of the adhesive for optical members of the present invention, its physical properties, applications, etc. will be described.
[0016] (A) Aromatic Hydrocarbon Resin The (A) aromatic hydrocarbon resin may be any resin having a total light transmittance of 80% or more in the visible light region at a thickness of 1 mm as measured in accordance with JIS K7361-1, having an aromatic ring in its structure, and being composed mainly of carbon and hydrogen. The adhesive for optical components may contain only one type of (A) aromatic hydrocarbon resin, or may contain two or more types.
[0017] The total light transmittance of the aromatic hydrocarbon resin (A) is preferably 85% or more, and more preferably 90% or more. The total light transmittance is a value obtained by preparing a molded plate of the aromatic hydrocarbon resin (A) having a thickness of 1 mm, and measuring the total light transmittance of the molded plate using a haze meter. Examples of the haze meter include the NDH4000 haze meter manufactured by Nippon Denshoku Industries Co., Ltd. In addition, the visible light in this specification refers to light having a wavelength of 400 nm to 700 nm.
[0018] Examples of the aromatic hydrocarbon resin (A) having the above total light transmittance include styrene homopolymer, α-methylstyrene homopolymer, α-methylstyrene / styrene copolymer, styrene / aliphatic polymer, α-methylstyrene / styrene / aliphatic copolymer, and partially hydrogenated products thereof. Among these, styrene homopolymer, α-methylstyrene homopolymer, α-methylstyrene / styrene copolymer, and partially hydrogenated products thereof are more preferable. These components have high total light transmittance and good compatibility with the (B) (meth)acrylic monomer and (C) rubber component described below.
[0019] The softening point of the (A) aromatic hydrocarbon resin is preferably from 50° C. to 200° C., more preferably from 60° C. to 150° C., and even more preferably from 80° C. to 130° C. When the (A) aromatic hydrocarbon resin has a softening point within this range, the stability of the cured product of the adhesive for optical components is further increased.
[0020] (A) Aromatic hydrocarbon resin may be a commercially available product. Examples of commercially available products include SYLVARES SA85, SYLVARES SA100, SYLVARES SA120, SYLVARES SA140 (all manufactured by Kraton Corporation); YS Resin SX100 (manufactured by Yasuhara Chemical Co., Ltd.); FTR0100, FTR2120, FTR2140, FTR6100, FTR6110, FTR6125, FTR7100, FTR8100, FTR8120, FMR0150 (all manufactured by Mitsui Chemicals, Inc.); Kristalex F85, Kristalex F100, Kristalex F115, Kristalex 1120, Kristalex 3070, Kristalex 3085, Kristalex 3100, Kristalex 5140 (all manufactured by Eastman Chemical Co., Ltd.), etc.
[0021] The total amount of the aromatic hydrocarbon resin (A) in the adhesive for optical components is preferably 10% by mass or more and 65% by mass or less, more preferably 30% by mass or more and 60% by mass or less. When the amount of the aromatic hydrocarbon resin (A) is 10% by mass or more, the cure shrinkage rate of the adhesive for optical components tends to be smaller. On the other hand, when the amount of the aromatic hydrocarbon resin (A) is 70% by mass or less, the amounts of the (meth)acrylic monomer (B) and the rubber component (C) become relatively sufficient, and the heat resistance and strength of the adhesive for optical components tends to be further improved.
[0022] (B) (Meth)acrylic monomer The (B) (meth)acrylic monomer in this specification may be one or more monomers selected from a mono(meth)acrylic monomer having one (meth)acrylic group in one molecule and a di(meth)acrylic monomer having two (meth)acrylic groups in one molecule. The adhesive for optical members may contain only one type of (B) (meth)acrylic monomer, or may contain two or more types.
[0023] Examples of mono(meth)acrylic monomers having one acrylic group in one molecule include monomers represented by the following general formula (B1). [ka]
[0024] In general formula (B1), R1 represents a hydrocarbon group having 4 to 18 carbon atoms. The hydrocarbon group having 4 to 18 carbon atoms may be a linear alkyl group, a branched alkyl group, an alicyclic structure, or a polycyclic hydrocarbon structure. It may also contain both of these structures. Meanwhile, R2 in general formula (B1) is a hydrogen atom or a methyl group.
[0025] Examples of the polycyclic hydrocarbon structure include structures represented by the following structural formulas. [ka]
[0026] Specific examples of the mono(meth)acrylic monomer represented by the above general formula (B1) include n-butyl(meth)acrylate, i-butyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, lauryl(meth)acrylate, i-stearyl(meth)acrylate, isoamyl(meth)acrylate, isodecyl(meth)acrylate, isooctyl(meth)acrylate, isomyristyl(meth)acrylate, tridecyl(meth)acrylate, cyclohexyl(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentenyl(meth)acrylate, isobornyl(meth)acrylate, and 1-adamantyl methacrylate.
[0027] An example of a di(meth)acrylic monomer having two (meth)acrylic groups in one molecule includes a monomer represented by the following general formula (B2). [ka] In the general formula (B2), R3 represents a hydrocarbon group having 4 to 12 carbon atoms. The hydrocarbon group having 4 to 12 carbon atoms may be a linear alkylene group or a branched alkylene group, which may contain an alicyclic structure. In addition, R4 and R5 in the general formula (B2) are each independently a hydrogen atom or a methyl group.
[0028] Specific examples of the di(meth)acrylic monomer represented by the above general formula (B2) include 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and the like.
[0029] Among the above, from the viewpoint of suppressing cure shrinkage during curing, a (meth)acrylic monomer having a polycyclic hydrocarbon structure is preferred, and dicyclopentenyl (meth)acrylate is particularly preferred.
[0030] The total amount of (B) (meth)acrylate monomer in the adhesive for optical members is preferably 20% by mass or more and 65% by mass or less, more preferably 30% by mass or more and 60% by mass or less. In addition, the total amount of (B) (meth)acrylate monomer is 30 parts by mass or more and 190 parts by mass or less, preferably 30 parts by mass or more and 190 parts by mass or less, more preferably 60 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of (A) aromatic hydrocarbon resin. As described above, when the amount is 30 parts by mass or more relative to 100 parts by mass of (A) aromatic hydrocarbon resin, the adhesive for optical members is easily photocured, and strength and heat resistance are easily increased. On the other hand, when the content of (B) (meth)acrylate monomer is 190 parts by mass or less, the curing shrinkage of the adhesive for optical members can be reduced.
[0031] (C) Rubber component having (meth)acrylic groups In this specification, the (C) rubber component having a (meth)acrylic group may be a compound in which a (meth)acrylic group is bonded to a rubber-like molecule such as polyurethane, polyisoprene, or polybutadiene. The (C) rubber component may be a liquid component at room temperature (25°C) or a solid component at room temperature (25°C). However, it is preferable that the component is soluble in the (B) (meth)acrylic monomer. The adhesive for optical members may contain only one type of the (C) rubber component, or may contain two or more types.
[0032] The structure of the rubber component (C) is not particularly limited, but is preferably a polyurethane (meth)acrylate oligomer, a polyisoprene (meth)acrylate oligomer, or a polybutadiene (meth)acrylate oligomer.
[0033] The polyurethane (meth)acrylate oligomer is an oligomer obtained by copolymerizing urethane, (meth)acrylic acid or (meth)acrylic acid ester, and other components as necessary. The polyurethane (meth)acrylate oligomer may be a random polymer or a block copolymer. The type of urethane in the polyurethane (meth)acrylate oligomer is not particularly limited, and may be an ether-based urethane, an ester-based urethane, or a carbonate-based urethane. The polyurethane (meth)acrylate may be a commercially available product, and an example of the polycarbonate urethane (meth)acrylate oligomer includes UN-9200A (manufactured by Negami Chemical Industries, Ltd.), and an example of the polyether urethane (meth)acrylate oligomer includes UN-6207 (manufactured by Negami Chemical Industries, Ltd.).
[0034] On the other hand, polyisoprene (meth)acrylate oligomer is an oligomer obtained by copolymerizing isoprene with (meth)acrylic acid, (meth)acrylic acid or (meth)acrylic acid ester, and optionally with other components. Polyisoprene (meth)acrylate oligomer may be a random polymer or a block copolymer. Polyisoprene (meth)acrylate oligomer may be a commercially available product, examples of which include U-102M and UC-203M (both manufactured by Kuraray Co., Ltd.).
[0035] The polybutadiene (meth)acrylate oligomer is an oligomer obtained by copolymerizing butadiene with (meth)acrylic acid or (meth)acrylic acid ester, and, if necessary, with other components. The polybutadiene (meth)acrylate oligomer may be a random polymer or a block copolymer. The polybutadiene (meth)acrylate oligomer may be a commercially available product, and examples thereof include TE2000 (manufactured by Nippon Soda Co., Ltd.).
[0036] In any structure of the (C) rubber component, the weight average molecular weight is preferably 5000 or more and 300,000 or less, and more preferably 10,000 or more and 100,000 or less. The weight average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography. When the (C) rubber component has a weight average molecular weight of 5000 or more, the extensibility of the adhesive for optical components tends to be further improved. On the other hand, when the (C) rubber component has a weight average molecular weight of 300,000 or less, the compatibility of the (C) rubber component with other components tends to be good.
[0037] The acrylic equivalent of the (C) rubber component is preferably 1000 g / mol or more and 20000 g / mol or less, more preferably 5000 g / mol or more and 10000 g / mol or less. In this specification, the acrylic equivalent is the value obtained by dividing the weight average molecular weight of the (C) rubber component by the number (average value) of acrylic groups and methacrylic groups that the (C) rubber component has in one molecule. When the acrylic equivalent of the (C) rubber component is in the above range, the photocurability of the adhesive for optical components tends to be good. On the other hand, the adhesive for optical components is less likely to undergo cure shrinkage, and the extensibility of the cured product of the adhesive for optical components tends to be good.
[0038] The total amount of the rubber component (C) in the adhesive for optical components is preferably 3% by mass or more and 40% by mass or less, more preferably 10% by mass or more and 30% by mass or less. When the amount of the rubber component (C) is within this range, the cured product of the adhesive for optical components tends to have good elongation. In addition, the total amount of the (B) (meth)acrylic monomer and the rubber component (C) per 100 parts by mass of the aromatic hydrocarbon resin (A) is preferably 50 parts by mass or more and less than 300 parts by mass, more preferably 50 parts by mass or more and 200 parts by mass or less. When the total amount of the (meth)acrylic monomer and the rubber component (C) is within this range, the photocurability of the adhesive for optical components tends to be good.
[0039] (D) Photopolymerization initiator The (D) photopolymerization initiator is not particularly limited as long as it is a compound capable of initiating polymerization of the (meth)acrylic group of the (B) (meth)acrylic monomer or the (C) rubber component. The (D) photopolymerization initiator may be a self-cleavage type photopolymerization initiator or a hydrogen abstraction type photopolymerization initiator. The adhesive for optical components may contain only one type of (D) photopolymerization initiator, or may contain two or more types.
[0040] Examples of the self-cleaving photopolymerization initiator include alkylphenone compounds (e.g., benzyl dimethyl ketal compounds such as 2,2-dimethoxy-1,2-diphenylethan-1-one (BASF, IRGACURE 651); α-aminoalkylphenone compounds such as 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one (BASF, IRGACURE 907); 1-hydroxy-cyclohexyl-phenyl-ketone (BASF, IRGACURE 907); 184) and other α-hydroxyalkylphenone compounds; acylphosphine oxide compounds such as 2,4,6-trimethylbenzoin diphenylphosphine oxide; titanocene compounds such as bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium; diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2- acetophenone compounds such as 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone; phenylglyoxylate compounds such as methylphenylglyoxyester; benzoin ether compounds such as benzoin, benzoin methyl ether, benzoin isopropyl ether; and oxime ester compounds such as 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)] (BASF, IRGACURE OXE01), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime) (BASF, IRGACURE OXE02).
[0041] Examples of the hydrogen abstraction type photopolymerization initiator include benzophenone compounds such as benzophenone, o-benzoylmethylbenzoate-4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone; and thioxanthone, 2-chlorothioxanthone (Tokyo Chemical Industry Co., Ltd.), 1-chloro-4-propoxythioxanthone, 1-chloro-4-ethoxythioxanthone (Lambson Limited, Speedcure CPTX), 2-isopropylxanthone (Lambson Limited, Speedcure ITX), 4-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone (Lambson Limited, Speedcure ITX). Examples of anthraquinone-based compounds include thioxanthone compounds such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-t-butylanthraquinone, 1-chloroanthraquinone, 2-hydroxyanthraquinone (Tokyo Chemical Industry Co., Ltd., 2-Hydroxyanthraquinone), 2,6-dihydroxyanthraquinone (Tokyo Chemical Industry Co., Ltd., Anthraflavic Acid), and 2-hydroxymethylanthraquinone (Junsei Chemical Co., Ltd., 2-(Hydroxymethyl)anthraquinone); and benzyl compounds.
[0042] The absorption wavelength of the (D) photopolymerization initiator is not particularly limited, and it is preferable that the photopolymerization initiator absorbs light having a wavelength of 360 nm or more, and it is particularly preferable that the photopolymerization initiator absorbs light having a wavelength of 365 to 425 nm. When the photopolymerization initiator has an absorption wavelength in this range, the photocurable adhesive can be cured satisfactorily by irradiation with light in this wavelength range.
[0043] Examples of photopolymerization initiators that absorb light with a wavelength of 360 nm or more include alkylphenone-based compounds, acylphosphine oxide-based photopolymerization initiators, titanocene-based photopolymerization initiators, oxime ester-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and anthraquinone-based photopolymerization initiators, of which oxime ester-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and anthraquinone-based photopolymerization initiators are preferred, and oxime ester-based photopolymerization initiators are particularly preferred.
[0044] The molecular weight of the (D) photopolymerization initiator is preferably, for example, 200 or more and 5000 or less. When the (D) photopolymerization initiator has a molecular weight of 200 or more, the handleability is likely to be good. On the other hand, when the molecular weight is 5000 or less, the compatibility of the (D) photopolymerization initiator with other components is likely to be increased. The molecular weight of the photopolymerization initiator is more preferably 230 or more and 3000 or less, and further preferably 230 or more and 1500 or less.
[0045] The molecular weight of the (D) photopolymerization initiator can be determined as the "relative molecular mass" of the molecular structure of the main peak detected when analyzed by high performance liquid chromatography (HPLC). Specifically, a sample solution is prepared by dissolving the (D) photopolymerization initiator in THF (tetrahydrofuran), and high performance liquid chromatography (HPLC) measurement is performed. Then, the area percentage of the detected peak (the ratio to the total area of each peak) is obtained, and the presence or absence of a main peak is confirmed. The main peak refers to the peak with the highest intensity (the peak with the highest height) among all peaks detected at a detection wavelength characteristic of each compound (for example, 400 nm for thioxanthone compounds). The relative molecular mass corresponding to the peak apex of the detected main peak can be measured by liquid chromatography mass spectrometry (LC / MS).
[0046] The total amount of the photopolymerization initiator (D) in the adhesive for optical components is preferably from 0.1% by mass to 10% by mass, more preferably from 1.0% by mass to 5.0% by mass. When the total amount of the photopolymerization initiator (D) is within this range, the adhesive for optical components tends to have good curing properties.
[0047] (E) Silane coupling agent The (E) silane coupling agent is a component for enhancing adhesion between the cured product of the adhesive for optical components and the optical components. The type of the (E) silane coupling agent is not particularly limited, and any known silane coupling agent can be used. The adhesive for optical components may contain only one type of (E) silane coupling agent, or may contain two or more types.
[0048] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-(meth)acryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane, 8-glycidoxyoctyltrimethoxysilane, methacryloxyoctyltrimethoxysilane, 8-vinyloctyltrimethoxysilane, and the like.
[0049] The total amount of (E) silane coupling agents in the adhesive for optical components is preferably 0.5% by mass or more and 10% by mass or less, and more preferably 1.0% by mass or more and 5.0% by mass or less. When the total amount of (E) silane coupling agents is within this range, the adhesive for optical components tends to have good curing properties.
[0050] (F) Other Ingredients The adhesive for optical members may further contain other components as necessary. Examples of the other components include antioxidants, leveling agents, defoamers, stabilizers, polymerization initiators, antiaging agents, wettability improvers, surfactants, plasticizers, UV absorbers, preservatives, and antibacterial agents. The adhesive for optical members may contain only one of these, or may contain two or more of them.
[0051] (G) Method for preparing adhesive for optical components The method for preparing the adhesive for optical components is not particularly limited, and all the components may be mixed at once, or the components may be mixed in two or more batches. For example, (A) aromatic hydrocarbon resin, (B) (meth)acrylic monomer, and (C) rubber component may be mixed first, and then (D) photopolymerization initiator, (E) silane coupling agent, etc. may be mixed.
[0052] During mixing, heating may be performed as necessary. The heating temperature is appropriately selected depending on the type and softening point of the (A) aromatic hydrocarbon resin, etc., and is preferably 80° C. to 150° C., and more preferably 100° C. to 140° C. Furthermore, the heating time is also appropriately selected, and is usually preferably 30 minutes to 120 minutes, and more preferably 40 minutes to 80 minutes.
[0053] (H) Physical properties of adhesives for optical components The viscosity of the adhesive for optical members is appropriately selected depending on the application of the adhesive for optical members, but for example, the viscosity measured at 23°C with an R-type viscometer is preferably 100 mPa·s to 100,000 mPa·s, more preferably 300 mPa·s to 7,000 mPa·s. If the viscosity of the adhesive for optical members is within this range, when the adhesive for optical members is used to bond optical members having uneven portions on the bonding surface, the adhesive for optical members easily penetrates into the uneven portions. In addition, the adhesive for optical members can be easily applied by various application devices.
[0054] The curing conditions for the adhesive for optical components are appropriately selected depending on the type of the photopolymerization initiator, but it can usually be cured by irradiation with ultraviolet light or visible light, and it is preferable to cure by irradiation with light having a wavelength of 365 nm to 425 nm. In this case, the integrated light amount per unit area is 1000 mJ / cm. 2 ~5000mJ / cm 2 is preferred, and 2000 mJ / cm 2 ~5000mJ / cm 2 When the adhesive for optical components is cured under such conditions, a cured product with high strength is obtained.
[0055] When the adhesive for optical components is cured, heating may be performed in addition to the light irradiation. The heating conditions are not particularly limited, but the heating temperature is usually preferably 40° C. or more and 110° C. or less, more preferably 60° C. or more and 90° C. or less. The heating time is usually 10 minutes or more and 120 minutes or less.
[0056] In addition, it is preferable that the cured product of the adhesive for optical members has excellent elongation. Specifically, the adhesive for optical members is applied to a thickness of 100 μm, and light having a wavelength of 365 nm is irradiated at 3000 mJ / cm. 2 When a tensile test is carried out on a cured product having a width of 10 mm and a length of 30 mm produced by irradiation at 25° C. and a tensile speed of 20 mm / min, the elongation at break is preferably 30% or more, more preferably 50% or more. The elongation at break is a value calculated by ([displacement length at break] / [length between chucks of the tensile tester at the start of measurement])×100. When the elongation at break of the cured product is 30% or more, the cured product of the adhesive for optical components is likely to follow deformations of the optical components and has good durability.
[0057] In addition, the cured product of the adhesive for optical members preferably has excellent light transmittance. Specifically, the average parallel light transmittance of the 100 μm-thick cured product of the adhesive for optical members at wavelengths of 380 nm to 780 nm is preferably 90% or more, more preferably 93% or more, and even more preferably 95% or more. When the parallel light transmittance of the adhesive for cured members is 90% or more, it is unlikely to affect the performance of optical elements, making it easy to use for various purposes. The parallel light transmittance can be determined by an ultraviolet-visible spectrophotometer.
[0058] Furthermore, the haze of the cured product of the adhesive for optical components having a thickness of 1 mm is preferably 7.0% or less, more preferably 6.0% or less, even more preferably 5.0% or less, and particularly preferably 3.0% or less. If the haze is within this range, the adhesive for optical components becomes difficult to visually recognize. The haze is measured with a haze meter.
[0059] The ratio of the refractive index at the D line of the cured product of the adhesive for optical components to the refractive index at the D line of the adherend (optical component) (refractive index of the cured product of the adhesive for optical components / refractive index of the adherend) is preferably 0.996 or more and 1.005 or less, more preferably 0.998 or more and 1.004 or less, and particularly preferably 1.000. The refractive index is a value measured with a multi-wavelength Abbe refractometer.
[0060] (I) Applications of adhesives for optical components The use of the adhesive for optical members is not particularly limited, and it can be used to bond optical members of various optical elements together or to bond an optical member to another member. As described above, the adhesive for optical members is unlikely to affect the metal film even when it is bonded to a bonding surface having a metal film. Therefore, it is very useful for bonding optical members having a metal film on the bonding surface. However, the adhesive for optical members has good adhesion not only to surfaces containing various metal films, but also to various inorganic materials and resins, for example. Therefore, it can be used in a wide range of applications. Examples of materials that can be bonded by the adhesive for optical members include glass, polyethylene terephthalate (PET), polycarbonate (PC), polymethyl methacrylate (PMMA), a composite of PC and PMMA, cyclic olefin copolymer (COC), cyclic olefin polymer (COP), etc.
[0061] 2. Optical elements Hereinafter, an optical element using the adhesive for optical members described above will be described, however, the optical element for which the adhesive for optical members can be used is not limited to this embodiment.
[0062] The optical element of the present invention includes a first optical member, a second optical member, and an adhesive layer that bonds them together, the adhesive layer being a cured product of the adhesive for optical members described above.
[0063] Examples of optical elements include optical imaging elements that combine two-dimensional or three-dimensional images or pictures in the air, such as the optical imaging device described in WO 2009 / 131128, the optical imaging device described in JP 2015-14777, the stereoscopic imaging device described in Japanese Patent No. 6203989, the stereoscopic imaging element described in JP 2018-13585, the optical imaging device described in JP 2011-90117, and the optical imaging means described in WO 2013 / 129063.
[0064] In the optical imaging element, the first optical member having a concave-convex portion and the second optical member having a concave-convex portion are arranged so that their concave-convex portions face each other. The concave-convex portions of the first optical member and the second optical member each consist of a plurality of linear ridges, and the plurality of ridges are arranged in parallel. A metal film such as an aluminum deposition film is arranged on a surface perpendicular to the thickness direction of the ridges, and the metal film is used as a light reflecting surface. In the optical imaging element, the adhesive layer is arranged between the first optical member and the second optical member so as to fill the concave-convex portions of the first optical member and the second optical member without any gaps, that is, adjacent to the first optical member and the second optical member.
[0065] The manufacturing method of the optical imaging element is not particularly limited, but for example, after arranging a first optical member and a second optical member in a predetermined direction, the above-mentioned adhesive for optical members is filled between the first optical member and the second optical member, and the adhesive for optical members is irradiated with light of a desired wavelength (e.g., ultraviolet light) and cured to obtain the optical imaging element.
[0066] Here, the optical imaging element may be an on-vehicle optical imaging element. An on-vehicle optical imaging element may be exposed to a high temperature and high humidity environment, and when a conventional adhesive for optical members is used to bond a first optical member and a second optical member, the adhesive layer may deteriorate over time. In contrast, when the first optical member and the second optical member are bonded together using the above-mentioned adhesive for optical members, the adhesive layer is less likely to deteriorate over a long period of time, and high adhesion to the first optical member and the second optical member can be maintained. EXAMPLES
[0067] The present invention will be specifically described below with reference to examples, but the scope of the present invention is not limited to the description of the examples.
[0068] 1. Material Preparation The following materials were used in the examples and comparative examples.
[0069] (A) Aromatic Hydrocarbon Resin FTR8100: Styrene-based polymer (FTR8100, Mitsui Chemicals, total light transmittance in the visible light region of 1 mm thickness measured according to JIS K7361-1: 91%) -Tamanol 803L: Terpene phenol-based tackifier (Tamanol 803L, manufactured by Arakawa Kogyo Co., Ltd., softening point: 155°C, Hazen color index (APHA): 450, total light transmittance in the visible light region at a thickness of 1 mm measured in accordance with JIS K7361-1: 60%) (B) (Meth)acrylic monomer F-512AS: Dicyclopentenyloxyethyl acrylate (Fancryl FA-512AS, manufactured by Resonac Corporation) (C) Rubber component having (meth)acrylic groups UC-102M: Polyisoprene methacrylate oligomer (UC-102, Kuraray Co., Ltd., number average molecular weight 17,000) (D) Photopolymerization initiator 184: 1-Hydroxycyclohexyl-phenyl ketone (Omnirad 184, IGM) TPO H: 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (Omnirad TPO H, manufactured by IGM) (E) Silane coupling agent KBM-403: 3-glycidoxypropyltrimethoxysilane (product name: KBM^403, manufactured by Shin-Etsu Chemical Co., Ltd.) (F) Other Ingredients Defoamer: Product name: BYK-1790, manufactured by BYK Japan Chain transfer agent: n-dodecyl mercaptan
[0070] 2. Preparation of adhesive for optical components (Examples 1 to 9 and Comparative Examples 1 to 8) (A) Aromatic hydrocarbon resin, (B) (meth)acrylic monomer, and (C) rubber component were charged into a flask in the composition (mass ratio) shown in Table 1 and heated at 120° C. for 1 hour. After that, it was cooled to room temperature (25° C.), and (D) photopolymerization initiator, (E) silane coupling agent, and (F) other components in the composition (mass ratio) shown in Table 1 were added and mixed to prepare an adhesive for optical components.
[0071] 3. Evaluation The adhesive for optical components was evaluated as follows. The results are shown in Table 1.
[0072] (1) Storage modulus Two polyethylene terephthalate (PET) films (thickness: 188 μm) with a size of 100 mm × 120 mm and subjected to a release treatment were prepared. A rectangular frame (dam) made of Teflon (registered trademark) with a thickness of 100 μm and a width of 10 mm was provided on the periphery of one of the PET films. Then, the adhesives for optical members prepared in the examples and comparative examples were respectively poured into the frame, and the other PET film was placed on top of the adhesives for optical members. Next, a conveyor-type UV irradiation device was used to irradiate the above-mentioned adhesives for optical members with light of a wavelength of 365 nm at an illuminance of 100 mW / cm. 2 The total light output is 3000mJ / cm 2 The cured product was measured using a dynamic viscoelasticity device (DMS6100, manufactured by SII NanoTechnology) at a measurement frequency of 10 Hz while increasing the temperature from 20°C to 140°C at a rate of 10°C / min, and the storage modulus E' (25°C) at 25°C was determined.
[0073] (2) Curing shrinkage rate The density of the adhesive for optical members before curing and the density of the sample after curing were measured with an automatic density meter (AccuPic II 1340, manufactured by Shimadzu Corporation). Then, the cure shrinkage was calculated by the following formula. Curing shrinkage rate (%) = {(density of sample after curing - density of adhesive for optical components before curing) / density of sample after curing} x 100
[0074] (3) Breaking Elongation A cured product of the adhesive for optical components was prepared in the same manner as in the measurement of the storage modulus (1) above. The cured product was then cut into a piece 10 mm wide and 30 mm long. After peeling off the two release films, the elongation at break of the cured product was measured using a tensile tester (Intesco Model 210, manufactured by Intesco Co., Ltd.). The measurement conditions were 25°C and a tensile speed of 20 mm / min, and the elongation at break (%) was calculated as ([displacement length at break] / [length between chucks at the start of measurement])×100. The results are shown in Table 1. ○: Elongation at break is 30% or more △: Elongation at break is 10% or more but less than 30% ×: Elongation at break is less than 10%
[0075] (4)Light transmittance A cured product of the adhesive for optical members was prepared in the same manner as in the measurement of the storage modulus in (1) above, except that the adhesive for optical members was sandwiched between two glass plates instead of a polyethylene terephthalate (PET) film that had been subjected to a release treatment. Next, the parallel light transmittance of the cured product having a thickness of 100 μm and the average light transmittance of the glass plate as a reference were measured using an ultraviolet-visible spectrophotometer (UV-2550, manufactured by Shimadzu Corporation). Then, the average value of the parallel light transmittance of the cured product having a thickness of 100 μm and the wavelength of 380 to 780 nm was calculated. The average value of the parallel light transmittance of the wavelength of 380 to 780 nm was taken as the average value of the parallel light transmittance for every 1 nm of wavelength when the wavelength was scanned from 380 nm to 780 nm.
[0076] (5) Adhesion Instead of glass plates, the adhesive for optical components was sandwiched between two plates made of cyclic olefin copolymer (COC), and the adhesive for optical components was cured to produce a laminate in the same manner as in the measurement of the storage modulus in (1) above. The obtained laminate was left in an environment of 80°C for 200 hours, and the appearance of the laminate was evaluated according to the following criteria. ○: No foaming or peeling at all ×: Foaming or peeling is observed in part or on the entire surface.
[0077] [Table 1]
[0078] As shown in the above table, in Examples 1 to 9, which contain (A) an aromatic hydrocarbon resin having a specific total light transmittance, (B) a (meth)acrylic monomer, (C) a rubber component having a (meth)acrylic group, (D) a photopolymerization initiator, and (E) a silane coupling agent, and in which the amount of (B) (meth)acrylic monomer relative to (A) the aromatic hydrocarbon resin is 30 parts by mass or more and 190 parts by mass or less, the cure shrinkage rate was 3.6% or less, which was sufficiently small. In addition, the elongation at break was 30% or more, and the light transmittance was 97% or more. Furthermore, the adhesion to the substrate after heating was also good.
[0079] In contrast, when the total light transmittance of the aromatic hydrocarbon resin in the visible light region at a thickness of 1 mm measured in accordance with JIS K7361-1 was less than 80%, the light transmittance of the obtained cured product was low (Comparative Example 3).
[0080] Furthermore, when the aromatic hydrocarbon resin (A) was not included, the cure shrinkage rate was likely to be large (Comparative Examples 1 and 8). Furthermore, when the amount of the (meth)acrylic monomer (B) relative to 100 parts by mass of the aromatic hydrocarbon resin (A) exceeded 190 parts by mass, the cure shrinkage rate was also likely to be large (Comparative Example 6).
[0081] On the other hand, when the rubber component (C) was not included (Comparative Example 4) or when the ratio of the (B) (meth)acrylic monomer and the rubber component (C) to the aromatic hydrocarbon resin (A) was low (Comparative Example 5), the elongation at break was likely to be low. When either the cure shrinkage rate or the elongation at break was evaluated low, the adhesion after heating was likely to be low (Comparative Examples 1 and 4 to 8). Even when these evaluations were good, the adhesion after heating was likely to be low when the silane coupling agent was not included (Comparative Example 2). [Industrial Applicability]
[0082] The adhesive for optical components of the present invention, even when used to bond optical components that include a metal film on the bonding surface, does not easily peel off the metal film and gives a cured product that is highly durable and has high optical transparency, and is therefore extremely useful in the manufacture of various optical elements.
Claims
1. (A) an aromatic hydrocarbon resin having a total light transmittance of 80% or more in the visible light region at a thickness of 1 mm as measured in accordance with JIS K7361-1; (B) one or more (meth)acrylic monomers selected from a mono(meth)acrylic monomer having one (meth)acrylic group in one molecule and a di(meth)acrylic monomer having two (meth)acrylic groups in one molecule; (C) a rubber component having a (meth)acrylic group; (D) a photopolymerization initiator; and (E) a silane coupling agent; Including, The amount of the (B) (meth)acrylic monomer relative to 100 parts by mass of the (A) aromatic hydrocarbon resin is 30 parts by mass or more and 190 parts by mass or less. Adhesive for optical components.
2. a total amount of the (B) (meth)acrylic monomer and the (C) rubber component having a (meth)acrylic group relative to 100 parts by mass of the (A) aromatic hydrocarbon resin is 50 parts by mass or more and less than 300 parts by mass; The adhesive for optical components according to claim 1 .
3. The (C) rubber component having a (meth)acrylic group is at least one selected from the group consisting of a polyurethane (meth)acrylate oligomer, a polyisoprene (meth)acrylate oligomer, and a polybutadiene (meth)acrylate oligomer. The adhesive for optical components according to claim 1 .
4. It is coated to a thickness of 100 μm and irradiated with light of 365 nm wavelength at 3000 mJ / cm 2 A cured product having a width of 10 mm and a length of 30 mm produced by irradiation is subjected to a tensile test at 25°C at a tensile speed of 20 mm / min. The elongation at break is 30% or more. The adhesive for optical components according to claim 1 .
5. At least a part of the adhesive surface of the adherend includes a metal film; The adhesive for optical components according to claim 1 .
6. a first optical member, a second optical member, and an adhesive layer that bonds the first optical member and the second optical member; The adhesive layer is a cured product of the adhesive for optical members according to claim 1. Optical elements.
7. The first optical member and / or the second optical member includes a metal film in an area adjacent to the adhesive layer. The optical element according to claim 6.
8. At least one of the first optical member and the second optical member has an uneven portion in a region adjacent to the cured product. The optical element according to claim 6.
9. An optical imaging element, The optical element according to claim 6.
10. It is an optical imaging element for automotive use. The optical element according to claim 6.
Citation Information
Patent Citations
Method for producing optical member, and adhesive
JP2022027270A